2017
DOI: 10.18596/jotcsa.317771
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cesium From Aqueous Solution by Adsorption Onto Si̇vas-Yildizeli̇ (Turki̇ye) Vermiculite: Equilibrium, Kinetic and Thermodynamic Studies

Abstract: In this study, cesium adsorption performance of raw vermiculite obtained from Sivas-Yıldızeli region of Turkey was investigated using batch adsorption method. In order to obtain the optimum adsorption conditions; different adsorbent dosages, contact times, solution pH's, initial cesium concentrations and temperature ranges were investigated. The concentration of cesium in solution was determined by ICP-OES. Kinetic studies demonstrated that adsorption process was in accordance with pseudo-second order kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The 1/ n values of the Si-CPTS-AHAP adsorbent are shown in Table 3 , where a value of <1 is an indication of high adsorption density. 73 The K F values as shown in Table 3 show that the newly synthesized Si-CPTS-AHAP adsorbent shows high adsorption of Cr( vi ) metal ions from aqueous solution and industrial wastewater (0.50 and 0.10 mol L −1 ). 74 Values of n > 1 are indicative of suitable adsorption conditions.…”
Section: Resultsmentioning
confidence: 94%
“…The 1/ n values of the Si-CPTS-AHAP adsorbent are shown in Table 3 , where a value of <1 is an indication of high adsorption density. 73 The K F values as shown in Table 3 show that the newly synthesized Si-CPTS-AHAP adsorbent shows high adsorption of Cr( vi ) metal ions from aqueous solution and industrial wastewater (0.50 and 0.10 mol L −1 ). 74 Values of n > 1 are indicative of suitable adsorption conditions.…”
Section: Resultsmentioning
confidence: 94%
“…These findings were in accord with previous reports where the Freundlich isotherm gives better conformation for the sorption of CV by various adsorbents (31,32). Furthermore, the 1/n value (0.56) demonstrates higher heterogeneity and that physical adsorption administrates the uptake of the dye by the porous carbon (33). The Langmuir model also yield a relatively good match (R 2 = 0.9869), implying compatibility of the data to the model.…”
Section: Isotherm Studiesmentioning
confidence: 88%
“…The chemical ion exchange happened for the E value 8−16 kJ/mol. The physical and chemical adsorptions occurred when E < 8 and E > 16 kJ/mol, respectively [28]. As shown in Table 1.…”
Section: Dubinin-radushkevich (D-r) Isothermmentioning
confidence: 93%
“…A plot of qe versus lnCe yielded linear lines which enable the determination of the isotherm constants KT and BT from intercepts and slope respectively [24]. Temkin isotherm constant bT derived from BT constant refers to the heat of adsorption and is used to determine the adsorption characteristics, meaning whether it is a physical or chemical process [28]. Empirical results demonstrated that adsorption of dyes onto adsorbents surface showed a physical sorption character since Temkin isotherm constant bT was found to be lower than 8 kJ/mol In addition, good linear regression value of 0.944 and 0.990 with RMC and MCAC respectively indicates that adsorption process is fits closely with Temkin isotherm model.…”
Section: Temkin Isothermmentioning
confidence: 99%